2018
DOI: 10.1186/s12906-018-2210-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile and biological properties of the leaves of Ficus vasta Forssk. (Moraceae) growing in Egypt

Abstract: BackgroundFicus vasta Forssk. (Moraceae) is traditionally used for the treatment of various ailments; nonetheless, this species has been poorly studied to date. This work aimed to characterize the phenolic profile and to evaluate the antioxidant and antimicrobial properties of a hydroalcoholic extract obtained from F. vasta leaves collected in Egypt.MethodsThe phenolic profile of the extract was characterized by HPLC-PDA/ESI-MS. The antioxidant properties were examined by different in vitro systems: DPPH test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…It is well known that polyphenols represent the main class of natural antioxidants, which act in different ways such as radical scavengers because phenolic groups are excellent nucleophiles and are also able to inhibit lipid peroxidation, as breakers of the oxidation reaction by binding with free radicals generated through lipid peroxidation, and as chelators of metal ions that induce oxidation [108]. Aimed at establishing the involvement of phenolic compounds in the antioxidant properties of I. tinctoria, recently, the polar extract obtained from the rosette leaves and also those from the cauline leaves and the flowers have been investigated by in vitro assays based on different mechanisms [47].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…It is well known that polyphenols represent the main class of natural antioxidants, which act in different ways such as radical scavengers because phenolic groups are excellent nucleophiles and are also able to inhibit lipid peroxidation, as breakers of the oxidation reaction by binding with free radicals generated through lipid peroxidation, and as chelators of metal ions that induce oxidation [108]. Aimed at establishing the involvement of phenolic compounds in the antioxidant properties of I. tinctoria, recently, the polar extract obtained from the rosette leaves and also those from the cauline leaves and the flowers have been investigated by in vitro assays based on different mechanisms [47].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Ficus genus is medically important due to the presence of high value of total bioactive contents (TPC and TFC) [ 62 ]. Previously, some flavonoid compounds were identified in leaves of F. vasta [ 25 ]. The high value of total phenolic and flavonoid contents in plant extract correlates with the strong antioxidant activities [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the antioxidant activity of the ethanolic extract in aerial parts of F. vasta has not been reported, while the methanol extract of F. vasta leaves showed the antioxidant activity [ 25 ]. The results of the DPPH, ABTS, FRAP, and CUPRAC activities showed that there is a direct link of antioxidant activities and the polyphenol contents (i.e., high value of phenolic and flavonoid contents correlates with the strong antioxidant activity) [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sabe-se que os ácidos fenólicos e flavonoides são os compostos mais abundantes da classe fenólica vegetal [35,36]. O ácido caféico, o ácido p-cumárico, o ácido ferúlico e o Kaempferol também já haviam sido identificados em amostras de OPN, mais especificamente como constituintes dos extratos hidrometanólicos (30:70, v/v) das folhas de Pereskia aculeata Miller [37].…”
Section: Fração Não Volátil (áCidos Fenólicos Flavonoides E Alcaloides)unclassified